Visual strategies of sustainability communication on corporate webpages. A critical multimodal discourse analysis in the hospitality sector - Ana María Fernández Vallejo (Ibérica, 2023)
Anchored in the methodology of digital corporate communication, multimodal discourse analysis, legitimation and relevance theories, the research focuses on the contribution of images – photographs and logos– to sustainability meanings conveyed by the websites to the different stakeholders. The corpus analysis includes 330 images coming from the five hotel chains most sustainable according to the Sustainability Yearbook 2022. These images were downloaded manually from the English corporate websites and particularly from the sites with the header and sub-header related to sustainability. The research procedure was organized in three phases from a quantitative and qualitative perspective by answering the questions: “what do you see?”, “what should the images represent regarding sustainability issues?” and “how visual elements are utilized to convey the different dimensions of sustainability on web pages?”. The results obtained show that, on the one hand, the hotel chains preferred photographs of people in order to elicit people's dimension and humanize their image and, on the other hand, the photographs of nature that depict planet dimension and would be the expected, are in the third position. With sustainability communication as a complex area of investigation, the aim of this paper is twofold. On the one hand, it aims at contributing to the studies of sustainability communication from a multimodal perspective. On the other hand, it aims at strengthening and furthering a methodological tool to critically analyse the sustainability discourse as a multimodal digital discursive practice.